Prostate Cancer Peripheral Blood NK Cells Show Enhanced CD9, CD49a, CXCR4, CXCL8, MMP-9 Production and Secrete Monocyte-Recruiting and Polarizing Factors - Gallazzi, Matteo; Baci, Denisa; Mortara, Lorenzo; Bosi, Annalisa; Buono, Giuseppe; Naselli, Angelo; Guarneri, Andrea; Dehò, Federico; Capogrosso, Paolo; Albini, Adriana; Noonan, Douglas M.; Bruno, Antonino (Frontiers in Immunology, 2021)
Natural killer (NK) cells, effector lymphocytes of the innate immunity, have been shown to be altered in several cancers, both at tissue and peripheral levels. We have shown that in Non-Small Cell Lung Cancer (NSCLC) and colon cancer, tumour associated circulating NK (TA-NK) and tumour infiltrating NK (TI-NK) exhibit pro-angiogenic phenotype/functions. However, there is still a lack of knowledge concerning the phenotype of peripheral blood (PB) NK (pNK) cells in prostate cancer (PCa). Here, we phenotypically and functionally characterized pNK from PCa patients (PCa TA-NKs) and investigated their interactions with endothelial cells and monocytes/macrophages. NK cell subset distribution in PB of PCa patients was investigated, by multicolor flow cytometry, for surface antigens expression. Protein arrays were performed to characterize the secretome on FACS-sorted pNK cells. Conditioned media (CM) from FACS-sorted PCa pTA-NKs were used to determine their ability to induce pro-inflammatory/pro-angiogenic phenotype/functions in endothelial cells, monocytes, and macrophages. CM from 3 different PCa (PC-3, DU-145, LNCaP) cell lines, were used to assess their effects on human NK cell polarization in vitro, by multicolor flow cytometry. We found that PCa pTA-NKs acquire the CD56brightCD9+CD49a+CXCR4+ phenotype, increased the expression of markers of exhaustion (PD-1, TIM-3) and are impaired in their degranulation capabilities. Similar effects were observed on heathy-donor derived pNK cells, exposed to conditioned media of three different PCa cell lines, together with increased production of pro-inflammatory chemokine/chemokine receptors CXCR4, CXCL8, CXCL12, reduced production of TNFα, IFNγ and Granzyme-B. PCa TA-NKs released factors able to support inflammatory angiogenesis in an in vitro model and increased the expression of CXCL8, ICAM-1 and VCAM-1 mRNA in endothelial cells. Secretome analysis revealed the ability of PCa TA-NKs to release pro-inflammatory cytokines/ chemokines involved in monocyte recruitment and M2-like polarization. Finally, CMs from PCa pTA-NKs recruit THP-1 and peripheral blood CD14+ monocyte and polarize THP-1 and peripheral blood CD14+ monocyte-derived macrophage towards M2-like/TAM macrophages. Our results show that PCa pTA-NKs acquire properties related to the pro-inflammatory angiogenesis in endothelial cells, recruit monocytes and polarize macrophage to an M2-like type phenotype. Our data provides a rationale for a potential use of pNK profiling in PCa patients.